Assessing the Economic Impact of Coffee Farming on Rural Communities in Colombia - Fernando, David (International Journal of Agriculture, 2024)
Purpose: The aim of the study was assessing the economic impact of coffee farming on rural communities in Colombia Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Assessing the economic impact of coffee farming on rural communities in Colombia reveals significant findings. Coffee farming is a major source of employment and a primary contributor to household income in these areas, supporting the economic stability of numerous families. Moreover, the coffee industry's demand for labor not only boosts local employment rates but also contributes to regional economic development through the generation of export revenues. Unique Contribution to Theory, Practice and Policy: Dependency theory, livelihoods approach & dual economy model may be used to anchor future studies on assessing the economic impact of coffee farming on rural communities in Colombia. Implement CBPR methods to involve coffee farmers in the research process, ensuring that their firsthand experiences and insights inform the study. Advocate for policies that support fair trade practices.